Competitiveness of colombian departments observed from an economic geography perspective (2007)
ABSTARCT: In this paper, we analyze the regional competitiveness concept and its measurement using the old and New Trade Theory and the New Economic Geography. The analysis shows that the competitiveness has no sense when is applied to the goods market, while has sense (however, not in all situations) when is applied to the productive factors market. Contrary to most approaches and measurements of the competitiveness of Colombian departments, we show that is possible to obtain simple measures which, in addition to being consistent with the conceptual framework of economic geography, are the product of the combination of a small number of variables.